2018
DOI: 10.1111/ans.14875
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality in cervical spine injuries in the elderly

Abstract: Background: The aim of our study was to identify the demographics and complications in elderly cervical spine injuries and predictive factors for surgery, complications and mortality. We hypothesized younger healthier patients were more likely to undergo surgical intervention. Methods: A retrospective review of 225 consecutive patients aged 65 years and over with cervical spine injuries was carried out over a 3-year period. Results: There were 113 males and 112 females with an average of 79.7 years (range 65-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
0
20
1
Order By: Relevance
“…This is consistent with the findings by Martin and coworkers, 20 who described an ''inflection point'' at the age of 75 for in-hospital mortality following cervical SCI. Our overall in-hospital mortality rate of 16% is slightly lower than the 12-40% reported by others, [15][16][17][18][19][20] but our data may underestimate the rate, as some patients who died shortly after admission may not have been enrolled in the registry.…”
Section: Relation To Literaturecontrasting
confidence: 80%
See 2 more Smart Citations
“…This is consistent with the findings by Martin and coworkers, 20 who described an ''inflection point'' at the age of 75 for in-hospital mortality following cervical SCI. Our overall in-hospital mortality rate of 16% is slightly lower than the 12-40% reported by others, [15][16][17][18][19][20] but our data may underestimate the rate, as some patients who died shortly after admission may not have been enrolled in the registry.…”
Section: Relation To Literaturecontrasting
confidence: 80%
“…14 A tSCI is both a devastating physiological and psychological insult for all patients, particularly in the elderly who often have multiple pre-existing comorbidities. In-hospital mortality rates in elderly patients with tSCI are reported as being 12-40%, [15][16][17][18][19][20] considerably higher than the estimated mortality of <5% in younger patient populations. 16 Previously identified risk factors for mortality in the elderly include older age, higher cervical level of injury, neurological severity, and increasing number of comorbidities; 17,18,20 however, to our knowledge, no one has developed a clinical decision-making aid using a combination of these factors for in-hospital mortality for this elderly population.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We found a number of factors associated with increased complication risk that is consistent with prior reports in the literature. In a retrospective review of 225 consecutive patients, Bokhari et al 21 found that neurological deficits, comorbidities, and presence of other injuries were predictors of complications and death. Similarly, we also found that the presence of at least one comorbidity increased the odds of having at least one complication.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the upper cervical spine represent a serious entity including a wide spectrum of pathology ranging from benign to life threatening [1]. Especially in the elderly, these injuries are not uncommon and their incidence will continue to grow due to increasing life expectancy and higher activity levels of the elderly population [5][6][7][8][9]. Currently, the emphasis centers on surgical treatment to obtain good alignment and stability to allow early mobilization.…”
Section: Introductionmentioning
confidence: 99%